Applied Mineralogy of Lead Sinter and Lead Blast Furnace Slag from Doe Run Corporation's Herculaneum Smelter - Susanne Pignolet-Brandom (The Minerals, Metals and Materials Society, 1987)
Reflected light microscopy scanning electron microscope energy dispersive spectroscopic analysis and backscatter electron image and electron microprobe chemical analysis have been used to study lead sinter and lead blast furnace slag. These studies provide invaluable information on the phases present their intergrowths, and their chemical composition. Such information increases the understanding of the nature of pyrometallurgical processes and the behavior of minor elements during these metallurgical processes.